Chimeric anterolateral thigh free flap for reconstruction of complex cranio-orbito-facial defects after skull base cancers resection. Issue 1 (January 2017) - Cherubino, Mario; Turri-Zanoni, Mario; Battaglia, Paolo; Giudice, Marco; Pellegatta, Igor; Tamborini, Federico; Maggiulli, Francesca; Guzzetti, Luca; Di Giovanna, Danilo; Bignami, Maurizio; Calati, Carolina; Castelnuovo, Paolo; et al.
Abstract: Complex cranio-orbito-facial defects after skull base cancers resection entail a functional and esthetic reconstruction. The introduction of endoscopic assisted techniques for excision surgery with the advances in reconstructive surgery and anesthesiology allowed to improve the management of such critical patients. We report a series of chimeric anterolateral thigh (ALT) flaps used to reconstruct complex cranio-orbital-facial defects after skull base surgery. A retrospective review of patients that underwent cranio-orbito-facial reconstruction using a chimeric ALT flap from March 2013 to October 2015 at a single tertiary care referral Institute was performed. All patients were affected by locally-advanced malignant tumor and the resulting defects involved the skull base in all cases. The ALT flaps were perforator-based flaps with different components: fascia, skin and muscle. The different flap territories had independent vascular supply and were independent of any physical interconnection except where linked by a common source vessel. Ten patients were included in the study. Three patients underwent adjuvant radiotherapy and to chemotherapy. The mean hospitalization time was 21 days (range, 8–24 days). One failure was observed. After a mean follow-up of 12.4 months, 3 patients died of the disease, 2 are alive with disease, while 5 patients (50%) are currently alive without evidence of disease. Chimeric ALT flap is a reliable and versatile reconstructive option for complex cranio-orbito-facial defects resulting from skull base surgery. The chimeric flap composed of different territories proved to be adequate for a patient-tailored three-dimensional reconstruction of the defects as well as able to resist to the postoperative adjuvant treatments.